Pengaruh Servicescape Terhadap Kepuasan Tamu Di Function Room Hotel The Axana Padang - Jefi Andas Pratama; Pasaribu Pasaribu (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
Abstract This research originated from the results of PLI 2 along with pre-research results for guests using the function room at the Axana Hotel in Padang. The purpose of this study was to determine the effect of servicescape on guest satisfaction at the Hotel Axana Padang function room. This type of research is quantitative with an associative causal approach. The number of samples of this study is 98 people with the sampling technique is purposive sampling. Data collection techniques are by distributing questionnaires (questionnaires) using the Likert scale method that has been tested for validity and reliability. Then the data were analyzed using simple linear regression with the help of the SPSS version 16.00 program. The results showed that Servicescape was in the very good category with a percentage of 89.90% and guest satisfaction was in the excellent category with a percentage of 71.43%, and there was a influence of servicescape variables on guest satisfaction by 39% while 61% was influenced by other factors. Keywords: Servicescape, Guest Satisfaction, Function Room